2012
DOI: 10.1016/j.jprot.2011.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane proteomes of differentially matured dendritic cells identified by LC–MS/MS combined with iTRAQ labelling

Abstract: Dendritic cells (DCs) play a pivotal role in polarising Th lymphocyte subsets but it is unclear what molecular events occur when DCs generate Th2-type responses. Here, we analysed plasma membrane-enriched fractions from immature, pro-Th1 and pro-Th2 DCs and used a combination of iTRAQ labelling and LC–MS/MS to quantify changes in the proteomes. Analysis was performed on triplicate biological samples and changes verified by flow cytometry. MHC class II molecules and CD29 were up-regulated in pro-Th1 DCs whilst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…We found that the ability of LNFPIII-NGC to alternatively activate APCs that drive CD4 ϩ Th2 responses is dependent on APC endocytosis of LNFPIII-NGC, as APCs treated with dynasore failed to drive CD4 ϩ Th2 responses. These results are similar to an earlier study suggesting that DC2s generated by activation with SEA had a distinct phenotype that included upregulation of clathrin and the endosomal marker Rab5 (54). The study by Ferret-Bernard et al strengthens our observation that dynamin/clathrin-mediated endocytosis of LNFPIII-NGC induces Th2-type immune responses (54).…”
Section: Discussionsupporting
confidence: 92%
“…We found that the ability of LNFPIII-NGC to alternatively activate APCs that drive CD4 ϩ Th2 responses is dependent on APC endocytosis of LNFPIII-NGC, as APCs treated with dynasore failed to drive CD4 ϩ Th2 responses. These results are similar to an earlier study suggesting that DC2s generated by activation with SEA had a distinct phenotype that included upregulation of clathrin and the endosomal marker Rab5 (54). The study by Ferret-Bernard et al strengthens our observation that dynamin/clathrin-mediated endocytosis of LNFPIII-NGC induces Th2-type immune responses (54).…”
Section: Discussionsupporting
confidence: 92%
“…Although transgelin‐2 has been mainly studied within T cells, B cells, and macrophages, there have been other immune cell types that have been reported to express transgelin‐2, such as dendritic cells (DCs). A proteomic analysis of differentially matured DCs demonstrated that transgelin‐2 expression was highly upregulated in some DC subpopulations . Moreover, it may be also worth mentioning that the DC cytoskeleton promotes T‐cell adhesion and activation via ICAM‐1 avidity alteration .…”
Section: Discussionmentioning
confidence: 99%
“…The quantification is performed on MS/MS level by comparing the intensities of reporter ions (114-117 for 4-component kit and 113-119 and 121 for 8-component kit). iTRAQ technology coupled with MDLC-MS has been broadly utilized in quantitative proteomics as a means of screening the potential biomarkers [118][119][120][121][122][123][124]. However, the labeling processes were all performed offline.…”
Section: Chemical Labelingmentioning
confidence: 99%